Forms of Address in the Regulated Sphere of Communication: The Formation of a New Standard - T S Zhukova (Russian journal of linguistics: Vestnik RUDN, 2014)
The article is an attempt to interpret the formation of new standards of use of the forms of address in regulated spheres of communication. Regulated communication is considered as communication restricted by the rules of an organization or a socio-political institute, as well as the rules and standards of speech etiquette and corporate ethics adopted by an organization. It is noted that in modern linguistics there are no typically occurring the conservative and restrictive perception of standards. A new view on the nature of the standard is being formed: the standard must be as close to the communicative situation as possible. The trends in the formation of the standards are identified on the basis of the observation over modern word usage, the analysis of metalinguistic reflection of the native speakers and the surveys of preferable choices of form of address in a particular communicative situation. To conclude it is stressed that the new standards of functioning of the forms of address need further theoretical understanding of this problem, analysis and recommendations for the use of new forms.